2021
DOI: 10.1186/s12986-021-00608-6
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index outperforms conventional anthropometric assessments as predictor of diabetes mellitus in elderly Chinese: a population-based study

Abstract: Background This study assessed the performance of visceral adiposity index and body shape index in predicting diabetes mellitus (DM) risk and compared their predictive ability to that of body mass index and waist circumference. Methods Among 8249 consecutive subjects who attended the Nationwide Health Check Up System for Senior Citizens (≥ 65 years) between 2008 and 2018, we examined the associations of several adiposity indices with DM risk and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…Xia et al [ 11 , 27 ] reported that CVAI is a stronger predictor of prediabetes and diabetes than traditional indexes such as BMI and WC. Similarly, TZou et al [ 28 ] found that CVAI and VAI may serve as potential indicators of diabetes. In addition, some studies reported that VAI is correlated with the risk of macrovascular complications in diabetic population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 98%
“…Xia et al [ 11 , 27 ] reported that CVAI is a stronger predictor of prediabetes and diabetes than traditional indexes such as BMI and WC. Similarly, TZou et al [ 28 ] found that CVAI and VAI may serve as potential indicators of diabetes. In addition, some studies reported that VAI is correlated with the risk of macrovascular complications in diabetic population [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 98%
“…These results had significant heterogeneities as they covered different ethnic populations ( 14 ). Recently, visceral adiposity index (VAI), lipid accumulation product (LAP), and body shape index (ABSI), which are the products of WC, BMI, and blood lipids, have been proposed as reliable indexes of body fat accumulation, and they have been applied to the prediction of diabetes ( 15 17 ). With reference to VAI and considering the characteristic of body fat in the Asian population, the Chinese visceral adiposity index (CVAI) has been designed for the Chinese population; this surrogate indicator may be more sensitive than VAI, WC, and BMI to discriminate diabetes ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study were in line with the study conducted by Tsou et al that suggested that BMI was significantly associated with DM outcomes when the various anthropometric parameters were compared with P < 0.001 for BMI. However, on compiled analysis, VAI had the maximum AUC (0.66) compared with BMI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…With WC ( r = 0.97, P < 0.001) in men and women ( r = 0.83, P < 0.001), WC showed an association with DM. However, the AUC suggested that VAI is better than WC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%